2018
DOI: 10.1001/jama.2018.4657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravesical Instillation of Gemcitabine vs Saline Immediately Following Resection of Suspected Low-Grade Non–Muscle-Invasive Bladder Cancer on Tumor Recurrence

Abstract: clinicaltrials.gov Identifier: NCT00445601.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 40 publications
3
144
1
Order By: Relevance
“…Single‐dose postoperative chemotherapy has been shown to reduce the risk of recurrence , however, 67% of urologists in a national US sample never administer immediate postoperative therapy owing to lack of chemotherapy availability, expense, tumour depth/perforation uncertainty, or fear of toxic side effects . Recent results published by the SWOG group showed that single‐dose postoperative intravesical gemcitabine reduces recurrence by 20% in histologically confirmed low‐grade NMIBC at a median follow‐up of 4 years in a randomized prospective sample . This provides a more readily available, cheaper alternative to other chemotherapy agents for the immediate postoperative setting.…”
Section: Resultsmentioning
confidence: 99%
“…Single‐dose postoperative chemotherapy has been shown to reduce the risk of recurrence , however, 67% of urologists in a national US sample never administer immediate postoperative therapy owing to lack of chemotherapy availability, expense, tumour depth/perforation uncertainty, or fear of toxic side effects . Recent results published by the SWOG group showed that single‐dose postoperative intravesical gemcitabine reduces recurrence by 20% in histologically confirmed low‐grade NMIBC at a median follow‐up of 4 years in a randomized prospective sample . This provides a more readily available, cheaper alternative to other chemotherapy agents for the immediate postoperative setting.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized, double-blind, phase III trial of 406 patients with suspected low-grade non-muscle-invasive bladder cancer based on cystoscopic appearance showed that immediate post-TURBT instillation of gemcitabine reduced the rate of recurrence compared with saline instillation (placebo). 9 In the intention to treat analysis, 35% of patients treated with gemcitabine and 47% of those who received placebo had disease recurrence within 4 years (HR, 0.66; 95% CI, 0.48-0.90; P,.001). 9 Intravesical therapy for a previous non-muscle-invasive bladder cancer was allowed in the study if received at least 6 months before enrollment.…”
Section: Intravesical Therapymentioning
confidence: 99%
“…Existing data support this approach largely for low-volume, lowgrade disease. [9][10][11] Although selected mapping biopsies may be indicated in specific situations for lesions that are solid (sessile) or if Tis or high-grade disease is suspected (eg, planned partial cystectomy, definitive chemoradiotherapy, evaluation of an unexplained positive urine cytology, certain clinical trials), random biopsies rarely yield positive results, especially for low-risk tumors. 12 Therefore, mapping biopsies of normal-appearing urothelium are not necessary for most patients.…”
Section: Clinical Presentation and Workupmentioning
confidence: 99%
“…The transurethral resection of the bladder (TURB) is the usual management strategy for patients' diagnosis and treatment of low-grade NMIBC [14]. Immediate intravesical chemotherapy (usually mitomycin C) within 24 h of TURB was shown in some phase III clinical trials to decrease recurrence in selected patients [15][16][17]. Further treatment with intravesical induction (adjuvant) is advised for tumors with an intermediate or high risk of progression.…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%